RANCANG BANGUN BUCKET PADA MINI EXCAVATOR LISTRIK - Sugiyanto, Sugiyanto; Prihadianto, Braam Delfian; Harjono, Harjono; Estiko, Dendi Milnanda; Siswantoro, Soeadgihardo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The prime mover for the majority of heavy equipment units is still dominated by fossil fuel engines. Before starting innovation on expensive large excavator machines, innovation can be started with electric mini excavators which have almost the same working system but have affordable development costs. This research focuses on the bucket which is an indicator of the performance of an excavator unit. The research method used was designing, making, and testing a bucket attached to a mini excavator. The final objective of this research is to design the bucket components that are installed on the electric mini excavator and also determine the volume of the bucket when it is in the flat position (struck) and in the full position (heaped). Based on research that has been carried out, the bucket volume of the mini excavator props when it is in the flat position (struck) is 0.012 m3 or the equivalent of 16.8 kg of sand and when it is in the full position (heaped) it is 0.017 m3 or the equivalent of 23.8 kg of sand.